Difference in Z scores of placental weight and fetal/placental weight ratio by mode of delivery. Issue 12 (15th September 2019) - Matsuda, Yoshio; Itoh, Toshiya; Okada, Eisaku; Sasaki, Kemal; Itoh, Hiroaki; Kanayama, Naohiro
Abstract: Aim: The difference of placental weight (PW) and fetal/placental weight ratio (F/P) Z scores by mode of delivery is unclear. To investigate such differences and the actual conditions underlying the imbalance between fetal and placental growth. Methods: The data from Japanese database 2013 were assessed. Light‐for‐dates (LFD, n = 12 884), appropriate‐for‐dates ( n = 114 464) and heavy‐for‐dates ( n = 13 164) from 140 512 placentas/infants of mothers delivered a singleton infant. Using Z scores of PW and F/P based on the standard curves of a sex‐, parity‐ and gestational‐age‐specific PW and F/P, the rate of inappropriately heavy placenta according to the mode of delivery (vaginal [VD] vs cesarean [CS]) was investigated. Results: (i) The PW and F/P were heavier and bigger in VD than in CS, in each subgroup. In the LFD groups, the PW Z score in VD was higher than that in CS, whereas the F/P Z score was lower than in VD than that in CS. (ii) Data of single regression analyses between the PW Z score and F/P Z score in VD groups were different from those in CS, especially in LFD infants. (iii) In the LFD subgroups, the rates of inappropriately heavy placenta in VD ( n = 7781) and CS ( n = 5103) were 0.54% and 0.86%, respectively. Conclusion: Difference in the mode of delivery influenced the PW and F/P, and the rate of inappropriately heavy placenta is associated with mode of delivery among LFD infants. This methodology might give us a clue to search a useful way for identifying the high‐risk groups requiring postnatal counseling.